"Subjective factors of psychological health in adolescence" (Ta'limning zamonaviy transformatsiyasi, 2024)
Clarification of the concept of psychological health of adolescents and the content of its components; disclosure of the peculiarities of maintaining psychological health as a result of the interaction of subjective and objective factors of psychosocial development. It is mainly based on the internal psychological aspects of the adaptation of the adolescent personality to environmental, social, cultural factors. Psychological health in adolescence allows you to assess the possibilities of overcoming and maintaining various life difficulties that determine its psychological well-beingУточнить понятие психологического здоровья подростков и содержание его компонентов; раскрыть особенности сохранения психологического здоровья в результате взаимодействия субъективных и объективных факторов психосоциального развития. В ее основе лежат, главным образом, внутренние психологические аспекты адаптации личности подростка к средовым, социальным и культурным факторам.Психическое здоровье в подростковом возрасте позволяет оценить возможности преодоления и сохранения различных жизненных трудностей, определяет его психологическое благополучие.O’smirlarning psixologik salomatligi tushunchasi va uning tarkibiy qismlarining mazmunini aniqlashtirish; psixososyal rivojlanishning sub'ektiv va obektiv omillarining o'zaro ta'siri natijasida psixologik salomatlikni saqlashning o'ziga xos xususiyatlarini ochib berish. Asosan o’smir shaxsiyatining ekologik, ijtimoiy, madaniy omillarga moslashuvining ichki psixologik jihatlariga asoslanadi.O’smirlik davrida psixologik salomatlik turli xil hayotiy qiyinchiliklarni engish va saqlab qolish imkoniyatlarini baholashga imkon beradi uning psixologik farovonligini belgilaydi